Shaping school culture : pitfalls, paradoxes, and promises - Deal, Terrence E. 4 0 16; Peterson, Kent D.; 5 (San Francisco : Jossey-Bass, 2009)
Explores the importance of school culture and the symbolic roles of leaders in shaping cultural patterns and practices in school communities; and presents numerous examples that demonstrate how culture influences school functioning.
Includes bibliographical references and index.
Professional.
Keywords: 2 -- 0; 6; Educational leadership.;School environment.;Educational change.;Educational leadership -- 20 -- Case studies; 20; 2